2021
DOI: 10.1186/s41512-021-00110-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dynamic updating strategies for clinical prediction models

Abstract: Background Prediction models inform many medical decisions, but their performance often deteriorates over time. Several discrete-time update strategies have been proposed in the literature, including model recalibration and revision. However, these strategies have not been compared in the dynamic updating setting. Methods We used post-lung transplant survival data during 2010-2015 and compared the Brier Score (BS), discrimination, and calibration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…We selected the update method by finding the optimal integrated calibration index with minimal impact to discriminative performance. Most of the updating methods exhibited similar performance and all were superior to not updating, similar to other studies that employed model updating for other use cases 11 . In addition, our method included a lag equal to the follow-up period before updating the model to ensure that updating was done prospectively, unlike the approach by Schnellinger et al that was inherently retrospective 11 , which we found to be overly optimistic (see hyperparameter optimization and causal model design in Supplementary Fig.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…We selected the update method by finding the optimal integrated calibration index with minimal impact to discriminative performance. Most of the updating methods exhibited similar performance and all were superior to not updating, similar to other studies that employed model updating for other use cases 11 . In addition, our method included a lag equal to the follow-up period before updating the model to ensure that updating was done prospectively, unlike the approach by Schnellinger et al that was inherently retrospective 11 , which we found to be overly optimistic (see hyperparameter optimization and causal model design in Supplementary Fig.…”
Section: Discussionsupporting
confidence: 77%
“…There is an inherent tradeoff between stationarity and sample size in the update cohort 51 . While small temporal windows can follow the dynamics of the nonstationary changes in the data, they might not have enough power in samples to enable certain modeling approaches, while larger windows that have adequate sample sizes might not be able to follow quickly changing dynamics 11 . In order to strike the balance for this tradeoff, our approach was to determine the size of the window based on a combination of formulas that estimate the proper sample size for LR models 52 and to perform a hyperparameter optimization that estimates the proper sample size for the custom GLM model (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations